2016
DOI: 10.1016/j.jhealeco.2016.06.001
|View full text |Cite
|
Sign up to set email alerts
|

Decision rules for allocation of finances to health systems strengthening

Abstract: A key dilemma in global health is how to allocate funds between disease-specific “vertical projects” on the one hand and “horizontal programmes” which aim to strengthen the entire health system on the other. While economic evaluation provides a way of approaching the prioritisation of vertical projects, it provides less guidance on how to prioritise between horizontal and vertical spending. We approach this problem by formulating a mathematical program which captures the complementary benefits of funding both … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 25 publications
(24 reference statements)
0
20
0
Order By: Relevance
“…This means that the effects of such a measure could go beyond preventing and mitigating one particular type of outbreak. Such "policy spill-over effects" are rarely included [16].…”
Section: Introductionmentioning
confidence: 99%
“…This means that the effects of such a measure could go beyond preventing and mitigating one particular type of outbreak. Such "policy spill-over effects" are rarely included [16].…”
Section: Introductionmentioning
confidence: 99%
“…A previous study has shown how it is possible to identify the optimal balance between investments in interventions and efficiency-improving HSS using mathematical programming methods (Morton et al, 2016). The innovation is to introduce an additional decision variable y into the standard CEA formulation that indicates the expenditure on HSS.…”
Section: Typology Of Health System Strengtheningmentioning
confidence: 99%
“…Through the parameter y, HSS type1 is implicitly addressing the ease with which technical efficiency of a platform can be improved. The simplest case is to assume that y uniformly improves the effectiveness of all interventions (Morton et al, 2016). The optimization problem is thenmaximizeyγxivi0.25emsubject0.25emto0.25emy+xiciB0.25em;all0xi1;yLyyU…”
Section: Typology Of Health System Strengtheningmentioning
confidence: 99%
“…Related literature in the area of economic evaluation deals with issues related to constraints with respect to implementation of health care technologies in practice ( Fenwick et al, 2008 , Hoomans and Severens, 2014 ). Note that although our starting point was that of incremental economic evaluations targeted at decision makers who might not have the discretion to relax health care input constraints, such constraints itself signal that the health system needs strengthening in terms of health care inputs ( Morton et al, 2016 ).…”
Section: Conclusion and Recommendationsmentioning
confidence: 99%